2008
DOI: 10.1002/chem.200701090
|View full text |Cite
|
Sign up to set email alerts
|

New Chiral Lanthanide Amide Ate Complexes for the Catalysed Synthesis of Scalemic Nitrogen‐Containing Heterocycles

Abstract: New chiral binaphthylamido yttrium and ytterbium ate complexes with lithium and potassium counterions have been synthesised and characterised. X-ray structures have been obtained for [Li(thf)4][Ln{(R)-C20H12(NC5H9)2}2] (Ln=Yb, Y) and [K(thf)5][Yb{(R)-C20H12(NCH2CMe3)2}2] as isostructural complexes. The efficiency of these complexes for the enantioselective intramolecular hydroamination was examined. [Li(thf)4][Yb{(R)-C20H12(NC5H9)2}2] afforded the highest enantiomeric excess (up to 87 %) for the synthesis of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(39 citation statements)
references
References 40 publications
1
38
0
Order By: Relevance
“…As an important progress towards a convenient and rapid method for synthesizing catalysts we have demonstrated that in situ prepared catalysts afforded better results in terms of activity and enantioselectivity than isolated complexes. The best outcome for 8a was obtained using N-cyclopentyl substituted complex YbLi6 (Scheme 1) affording 87% ee as the highest enantiomeric excess with this series of complexes (entry 11) [16]. With the aim to get insight into the possible role of lithium in hydroamination/cyclization catalyzed by rare earth ate lithium complexes LnLi (Scheme 1), we prepared and characterized similar potassium rare earth complexes LnK (Scheme 3) [16].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…As an important progress towards a convenient and rapid method for synthesizing catalysts we have demonstrated that in situ prepared catalysts afforded better results in terms of activity and enantioselectivity than isolated complexes. The best outcome for 8a was obtained using N-cyclopentyl substituted complex YbLi6 (Scheme 1) affording 87% ee as the highest enantiomeric excess with this series of complexes (entry 11) [16]. With the aim to get insight into the possible role of lithium in hydroamination/cyclization catalyzed by rare earth ate lithium complexes LnLi (Scheme 1), we prepared and characterized similar potassium rare earth complexes LnK (Scheme 3) [16].…”
Section: Introductionmentioning
confidence: 98%
“…The best outcome for 8a was obtained using N-cyclopentyl substituted complex YbLi6 (Scheme 1) affording 87% ee as the highest enantiomeric excess with this series of complexes (entry 11) [16]. With the aim to get insight into the possible role of lithium in hydroamination/cyclization catalyzed by rare earth ate lithium complexes LnLi (Scheme 1), we prepared and characterized similar potassium rare earth complexes LnK (Scheme 3) [16]. The potassium ate catalysts coordinated by N-neopentyl and N-cyclopentyl substituted ligands revealed less efficient than the corresponding lithium complexes (Table 1, entries 13e15 compared to entries 1, 11 and 12), since longer reaction times were necessary and in most cases lower ee were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Chiral lanthanide complexes display high activity in enantioselective intramolecular hydroamination. [22] Also, application of non-transition-metal complexes as catalysts of hydroamination reactions has been reported. Thus, the a-diketiminate derivatives of magnesium and calcium serve well as precatalysts for the hydroamination/cyclization of aminoalkenes.…”
mentioning
confidence: 99%
“…The ate complexes [Li(THF) [53][54][55][56][57]60] are unusual hydroamination catalysts as they lack an obvious leaving amido or alkyl group that is replaced during the initiation step by the substrate. It is very likely that at least one of the amido groups is protonated during the catalytic cycle, analogous to the mechanism proposed for Michael additions and aldol reactions catalyzed by rare earth metal-alkali metal-BINOL heterobimetallic complexes [69,70].…”
Section: ð11:7þmentioning
confidence: 99%